Resistive switching in nanostructured thin films - Silva, Hugo G. (2014)
Planar capacitor structures based on granular films composed of nanometric ferromagnetic grains embedded in an insulating Al2O3 matrix can switch between a high-conductance and a low-conductance state. The switching properties are induced by a forming process. The ON/OFF resistance ratio is as high as 104 under an electrical field of only 15 kV/m. This resistive switching is accompanied by a capacitive switching between two well-defined voltage-independent states, a behavior that is not readily explained by the filamentary type of conduction.